Normocellular CSF in herpes simplex encephalitis - Saraya, Abhinbhen W. (BMC Res Notes, 2016)
BACKGROUND: Herpes simplex virus (HSV) is the most common cause of sporadic encephalitis worldwide. The high mortality rate (70–80 %) of herpes simplex encephalitis (HSE) can be reduced to 20–30 % by antiviral therapy. However, normocellular CSF can lure physicians to look for non-infectious causes, resulting in delayed treatment. This study aimed to investigate, characterize and differentiate HSE patients, with normocellular and pleocytosis CSF, according to neuroimaging patterns, underlying disease, CSF viral load and clinical outcome. Patients with proven (by PCR positive CSF) or presumed viral infections of the CNS admitted to King Chulalongkorn Memorial Hospital between January 2002 and 2011 were analyzed. RESULTS: HSV was detected in the CSF of 43 patients but only 23 patients had encephalitis. Among these 23 patients, 6 cases (26.1 %) had normal CSF WBC (<5 cells/mm(3)). One patient in this normocellular CSF group had HIV infection. Although this patient had low CD4 counts (<200 cells/mm(3)), the peripheral WBC counts showed only mild leukopenia. The CSF HSV viral load in the pleocytosis group was higher than the normocellular group, with an average of 12,200 vs 3027 copies/ml respectively. There was no correlation between the viral load and the clinical outcome. With respect to neuroimaging, 4 (66.7 %) patients in the normocellular group had unremarkable/non-specific results. CONCLUSIONS: Normocellular CSF in HSE is not rare, and can be seen in normal as well as immunocompromised hosts. Clinicians should not exclude CNS infection, especially HSE, merely based on the absence of CSF pleocytosis and/or unremarkable neuroimaging study.